Negosiasi Tradisi dan Keyakinan Keagamaan dalam Tari Raleng Tendi pada Masyarakat Karo di Desa Sibiru-biru - Aprilinda M. Harahap; Ismail Dasopang; Herviani Herviani; Rizka Naine Putri; Amanda Vidura Silalahi (Universitas Negeri Medan, 2026)
This study aims to analyze the negotiation process between cultural traditions and religious beliefs in the practice of the Raleng Tendi Dance among the Karo community in Sibiru-biru Village. The Raleng Tendi Dance is a tradition rooted in the Pemena belief system and originally functioned as a ritual to recall the tendi (soul) as part of a healing process. With the spread of formal religions such as Islam and Christianity, this tradition has undergone various adjustments in its implementation. This research employs a qualitative method with a descriptive approach through interviews with traditional leaders and religious leaders, supported by a literature review. The findings reveal that the Karo community has not entirely abandoned the Raleng Tendi Dance; instead, they have adapted and reinterpreted its ritual meanings. The tradition is maintained as a cultural identity while being adjusted to contemporary religious values. Based on Peter L. Berger’s Social Construction Theory, the negotiation process occurs through the stages of externalization, objectivation, and internalization, resulting in a new understanding that cultural preservation and religious practice can coexist harmoniously. This study demonstrates that the relationship between religion and culture in Karo society is more often manifested through accommodation and integration rather than conflict.